2021
DOI: 10.1111/dme.14650
|View full text |Cite
|
Sign up to set email alerts
|

‘Oh, I’ve got an appointment’: A qualitative interview study exploring how to support attendance at diabetes screening after gestational diabetes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Despite guidelines recommending that women who have been affected by GDM should be screened for glucose abnormalities during the postpartum period and beyond, uptake is typically low and a research team from Cambridge sought to explore the views of women with GDM about why. 2 They found that the current system is not easily compatible with family life, and suggest that greater flexibility in appointment location and times, including 'baby friendly' clinics, would be beneficial. Interestingly, the nature of the test itself was not found to be a barrier to attendance.…”
Section: Frailty Gestational Diabetes Shared Cancer Care and Positive Healthmentioning
confidence: 99%
“…Despite guidelines recommending that women who have been affected by GDM should be screened for glucose abnormalities during the postpartum period and beyond, uptake is typically low and a research team from Cambridge sought to explore the views of women with GDM about why. 2 They found that the current system is not easily compatible with family life, and suggest that greater flexibility in appointment location and times, including 'baby friendly' clinics, would be beneficial. Interestingly, the nature of the test itself was not found to be a barrier to attendance.…”
Section: Frailty Gestational Diabetes Shared Cancer Care and Positive Healthmentioning
confidence: 99%
“…Our previous systematic review informed the interview guide and suggestion cards, which were adapted from 20 recommendations (Fig 1 and S1 Table) [17]. The first part of the interview focused on diet and physical activity while the second part focused on screening for T2DM (reported separately [23]); ten suggestion cards were used as prompts in each part. We conducted three pilot interviews and collected written feedback from our patient and public involvement group, composed of mothers with GDM.…”
Section: Interview Processmentioning
confidence: 99%
“…due to natural distractions or initiating a different train of thought). We then discussed how to facilitate attendance at diabetes screening after GDM in the second part of the interview [23]. Finally, demographic information (including age band, ethnic group, employment status and pregnancy history) and interview feedback were collected through a short questionnaire.…”
Section: Plos Onementioning
confidence: 99%
“…15 Some women appreciate their GP reminding them about follow-up screening recommendations. 16 General reminder interventions have been found to increase participation in international studies, 13,[17][18][19] and a systematic review has indicated that reminder interventions were perceived as helpful by women. 15 However, only a single survey examined women's views on receiving a reminder.…”
Section: Introductionmentioning
confidence: 99%